Hyperhomocysteinemia and Cytokine Profiles in Henoch-Schönlein Purpura: Genetic Associations and Treatment Outcomes - Ormonbek Dzhakypbaev; Akmatbek Saparbaev; Rysbek Sadyjev; Asel Kenzheeva; Kunduz Shuku‑ ralieva; Nurzhan Usenova; Sagynali Mamatov (Trends in Immunotherapy, 2025)
Henoch-Schönlein purpura (HSP) is a systemic vasculitis characterized by purpura, joint pain, abdominal discomfort, and renal involvement in children. This study aimed to evaluate the homocysteine (Hcy) levels, polymorphisms of the methylenetetrahydrofolate reductase (MTHFR) C677T and methionine synthase (MTR) A2756G genes, and immunological parameters in 183 patients with HSP. Hyperhomocysteinemia (HHcy) was found in 67.5% of patients, with 66.6% and 7.4% of patients with HHcy having MTHFR C677T heterozygosity and homozygosity, respectively. MTR A2756G polymorphisms were present in 44.4% of patients with HHcy. Patients with both HHcy and gene mutations experience more severe symptoms. Flow cytometry revealed reduced CD4 and CD8 antigen expressions in some patients. Serum cytokine analysis showed significantly higher IL-6 and TNF-α levels in patients with generalized HSP than in controls and those with cutaneous-articular HSP. Immunomodulatory treatments, such as cyclosporin A and rituximab, were effective in severe, treatment-resistant cases, reducing symptoms and inflammatory markers in these patients. This study highlights the importance of genetic, metabolic, and immunological assessments in guiding personalized treatment for HSP. Recommendations include measuring Hcy levels, genotyping for MTHFR C677T and MTR A2756G polymorphisms, immunophenotyping, and considering immunomodulatory treatments in cases that are severe.